Samples & cell type composition in sc/snRNA-seq. - Jingxin Zeng (18773484) (2025)
Melanoma brain metastasis (MBM) remains lethal with limited treatment efficacy. Meanwhile, the cellular origins and drivers of brain metastasis from melanoma have yet to be defined. Through integrated single-cell/single-nucleus RNA sequencing of 26 melanoma samples, we identified a pre-brain-metastatic tumor subpopulation (MBMATCs, MBM-associated tumor cells) within a conserved malignant cell trajectory (Mela3). MBMATCs exhibited activated pro-metastatic pathways and upregulated neural/adhesion genes (NRG3, NCAM1), suggesting a cellular origin for brain tropism. MBM ecosystems showed T cell exhaustion (elevated PD-1, HAVCR2, LAG3) and Treg enrichment. An MBM-Index derived from bulk RNA-seq accurately quantifies MBMATCs abundance, independently predicting poor overall survival in both TCGA-SKCM and validation cohorts. Furthermore, we assessed the clinical relevance of the MBM-Index and uncovered five candidate drugs with potential activity against MBMATCs. This study identifies MBMATCs as brain metastasis associated tumor cells and positions the MBM-Index as a biomarker for early stratification of melanoma patients at high risk of brain metastasis.